A service-system paradigm for governing corporate sustainability: the (forgotten) role of governing body in shaping sustainability and context. (2016) - Hysa, Xhimi; Calabrese, Mario; Bilotta, Alberto; Salaj, Florjan
Corporate sustainability (CS), as an evolutionary concept, covers better many open questions and scientific confusion of corporate social responsibility (CSR). While CSR has not well defined the concept of environment, CS has recovered this gap ignoring at the same time the fundamental passage from environment to context and the context's architect/designer (i.e., the governing body, GB). Therefore, this study, after reviewing the barriers of a corporate-;context sustainability, shows how the GB, influenced by the components of information variety (i.e., information units, interpretation schemes and categorical values), contextualises the sustainability. A service-system conceptual model, based on viable systems approach (VSA) and service-dominant logic, constructs the foundations for consonance and value cocreation between the GB, context's suprasystems, general environment (e.g., other stakeholders) and international standards (e.g., GRI, Global Compact, etc.). The model integrates also the GRI-G4 report with subjective elements of the GB.